2020
DOI: 10.1101/2020.06.19.161554
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of sex differences in tumor-specific T cell infiltration in bladder tumor-bearing mice treated with BCG immunotherapy

Abstract: Bladder cancer is the fourth most common cancer for men. However, women are often diagnosed with later stage disease and have poorer outcomes. Whether immune-based sex differences contribute to this discrepancy is unclear. In addition, models to investigate tumorspecific immunity in bladder cancer, in the context of tumor development or response to therapy, are lacking. To address this specific unmet need, we incorporated a commonly used model antigen, ovalbumin, into two well-established models of bladder can… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…In the case of bladder cancer, AR antagonism may have a different outcome. We applied the BBN model to transgenic URO-Ova mice expressing a model antigen from the urothelium to follow tumor-specific T cell responses during immunotherapy 148 . We found that tumorspecific T cells infiltrated the bladder more robustly in male tumor-bearing mice treated with BCG and PD-L1 immunotherapies compared to female tumor-bearing mice, which may be one reason why men have better bladder cancer outcomes than women 148 .…”
Section: Taking Sex Into Account For Therapeutic Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of bladder cancer, AR antagonism may have a different outcome. We applied the BBN model to transgenic URO-Ova mice expressing a model antigen from the urothelium to follow tumor-specific T cell responses during immunotherapy 148 . We found that tumorspecific T cells infiltrated the bladder more robustly in male tumor-bearing mice treated with BCG and PD-L1 immunotherapies compared to female tumor-bearing mice, which may be one reason why men have better bladder cancer outcomes than women 148 .…”
Section: Taking Sex Into Account For Therapeutic Approachesmentioning
confidence: 99%
“…We applied the BBN model to transgenic URO-Ova mice expressing a model antigen from the urothelium to follow tumor-specific T cell responses during immunotherapy 148 . We found that tumorspecific T cells infiltrated the bladder more robustly in male tumor-bearing mice treated with BCG and PD-L1 immunotherapies compared to female tumor-bearing mice, which may be one reason why men have better bladder cancer outcomes than women 148 . Importantly, however, whether this difference is mediated by sex hormones, sex chromosomes, or another mechanism is unclear and would require preclinical studies modulating each of these factors before one could conclude that AR antagonism is a viable treatment approach.…”
Section: Taking Sex Into Account For Therapeutic Approachesmentioning
confidence: 99%